AB1331 Serum drug levels in the management of rheumatoid arthritisand spondyloarthritis: a systematic review. (12th June 2018) - Martín López, M.; Carmona, L.; Balsa, A.; Calvo-Alén, J.; Sanmartí, R.; Tornero, J.; Otón, T.; Rosas-Gómez de Salazar, J.
Abstract : Background: Several studies in rheumatic and other inflammatory diseases treated with tumour necrosis factor-alpha inhibitors (TNFi) support the association between clinical response and trough drug levels (DL). The utility of monitoring DL in rheumatoid arthritis (RA) and spondyloarthritis (SpA) patients on biological therapy is not clear, so it is important to identify clinical situations in which, the knowledge of DL, would allow an individualised therapeutic decision in the patient, more cost-effective. Objectives: To answer the most relevant clinical questions related to the usefulness of DL measurement in clinical practice: 1) whether, in patients in remission who are candidates for optimisation, DL predict relapse or survival to dose-titration; 2) whether, in patients with primary or secondary failure to biological agents, DL influence prognosis; and 3) whether concomitant use of methotrexate (MTX) influences the association between DL and response. Methods: An electronic search of the major databases was performed, Medline, Embase and Cochrane Library, from inception to December 2016. We included articles published in English or Spanish on patients with RA, SpA or both, treated with TNFi, tocilizumab or abatacept, and related to answer any of the three questions of the target research. Overall characteristics and outcomes of the studies were collected in a table of evidence and the quality of the studies was assessed with a scale based on the Oxford levels of Evidence. Results: The electronic search strategy yielded 1749 articles, twelve of which were included in this systematic review. 2 studies responded the first question, 5 the second, and 7 the third. These studies were mainly observational studies, 6 retrospective and 4 prospective cohort studies, and 2 randomised clinical trials. Sample sized varied from 24 to 395 patients, for a total of 1482 patients analysed. A total of 1281 RA patients were included (64 in the first question, 243 in the second and 1038 in the third) and 201 SpA patients (32 in the first and second questions, 169 in the third). Studies were small and with limitations, but suggest that measurement of DL may be useful in patients in remission, that higher DL predict a longer relapse-free optimisation, and in patients with failure to a biological agent, treatment may need individual adjustment according to the presence of DL or antidrug-antibodies. In addition, MTX influences the association between response and DL in most studies, with greater controversy in tocilizumab and SpA patients. Conclusions: Monitoring DL would allow optimal use of current biological therapies, but more studies and of better quality are needed to draw definitive conclusions. In addition, future research should be performed to determine therapeutic ranges of DL, so that the proposed algorithms can be used in a standardised and reliable manner. Disclosure of Interest: None declared